First Report of FVC and FEV1 Reference Values for Beninese Children Aged 11–16 Years. (13th August 2013) - Messan, Folly; Dansou, Pierre; Marqueste, Tanguy; Decherchi, Patrick; Tossou, Richard; Amoussou, Toussaint; Sovi-Guidi, Bénoîte
Abstract : Background . The diagnosis of obstructive ventilatory disorders in children in Benin is not reliable despite the inclusion of ethnic correction factors for European standards (ERS-93) and the use of African-American standards (ITS-Black). Objectives . (1) Define standard values for forced vital capacity (FVC) and forced expiratory volume in the first second (FEV1) and (2) compare the FVC and FEV1 values observed in study subjects to those calculated by the ERS-93 and ITS-Black equations. Methods . FVC and FEV1 were measured using the MicroQuark Spirometer (Cosmed, Italy), and standing height was measured in 274 Beninese boys and 210 Beninese girls. The means and 95% confidence intervals for these values were calculated by univariate analysis. Results . FVC and FEV1 values calculated using the ERS-93 equations were significantly higher (P < 0.05 ) than the measured values from our study. The percent change between the standard values in our study and the standards calculated using the ERS-93 and ITS-Black equations revealed differences between Beninese children and children of European or African-American descent. Conclusion . The differences observed between study samples and those derived from the ITS-Black and the ERS-93 equations should be used as ethnic correction factors.